2023
DOI: 10.3390/infrastructures8030040
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Surrogate Safety Measures and Road Design Characteristics towards Crash Investigations in Motorway Segments

Abstract: High quality data on road crashes, road design characteristics, and traffic are typically required to predict crash frequency. Surrogate Safety Measures (SSMs) are an alternative category of indicators that can be used in road safety analyses in order to quantify various unsafe traffic events. The objective of this research is to exploit road geometry data and SSMs toward various road crash investigations in motorway segments. To that end, for this analysis, a database containing data on injury and property-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…It can be observed that this representative motorway segment is more likely to belong to the lowest crash risk level, as denoted by the positive (green) bars of all predictors for this specific class. This crash risk level corresponds to overall safer locations with lower traffic volumes and road crashes by segment length than the motorway segments between the first and the third crash risk level [17]. It is worth noting that Figure 2 shows the contribution of only a subset of the variables that have been included in the multiclass classification RF model, as the other variables are not contributing much to the model's predictions and their contribution to the model's output can be, therefore, considered negligible.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…It can be observed that this representative motorway segment is more likely to belong to the lowest crash risk level, as denoted by the positive (green) bars of all predictors for this specific class. This crash risk level corresponds to overall safer locations with lower traffic volumes and road crashes by segment length than the motorway segments between the first and the third crash risk level [17]. It is worth noting that Figure 2 shows the contribution of only a subset of the variables that have been included in the multiclass classification RF model, as the other variables are not contributing much to the model's predictions and their contribution to the model's output can be, therefore, considered negligible.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, the Shapley additive explanations (SHAP) were estimated and provided as an attempt to deal with the interpretation of the best performing machine learning algorithm outcomes. It should be noted that the present research is an extension of the study that was conducted by Nikolaou et al, in which the motorway segments' risk levels were determined and the comparison of various ML classification models was proposed as a future research direction [17].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Following the definition proposed in Parker et al, 1988, a traffic conflict is "an event involving two or more road users, in which the action of one user causes the other user to make an evasive maneuver to avoid a collision". Such motion conflicts are commonly evaluated using surrogate safety measures (Nikolaou et al, 2023). While other methods to characterise a conflict have been proposed, the post encroachment time (PET) and time-to-collision (TTC) are commonly used surrogate safety measures to study conflict severity (Sayed et al, 1994, Hyden, 1987, Hayward, 1972, Orsini et al, 2023, Paul and Ghosh, 2020.…”
Section: Traffic Conflicts and Safety In Mixed Trafficmentioning
confidence: 99%
“…Transportation researchers utilise various techniques to understand the crash phenomenon, such as crash investigation reports, video analysis, naturalistic driving studies, simulation studies, crash data statistical analysis, artificial neural networks, surrogate safety measures, and telematics data analysis [4][5][6][7]. Safety performance functions (SPFs)statistical models for crash prediction-have been the subject of many studies during the past few decades [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%